2009
DOI: 10.1016/j.jvs.2008.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound as the sole long-term surveillance method post-endovascular aneurysm repair: A safe alternative for stable aneurysms

Abstract: CDU only surveillance post-EVAR is safe and can be initiated early after treatment in patients with shrinking or stable aneurysms. This policy should result in cost savings advantage and avoid the complications associated with CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 22 publications
0
86
1
1
Order By: Relevance
“…3,4 Additionally, USV is convenient, noninvasive, inexpensive and portable, does not involve radiation exposure and does not need contrast. However, there is a relatively higher rate of interobserver and intraobserver variability with ultrasonography than with angiotomography, 18 but this variability is no larger than 4 mm, on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Additionally, USV is convenient, noninvasive, inexpensive and portable, does not involve radiation exposure and does not need contrast. However, there is a relatively higher rate of interobserver and intraobserver variability with ultrasonography than with angiotomography, 18 but this variability is no larger than 4 mm, on average.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Compared with conventional surgery, endovascular repair offers low rates of perioperative mortality and morbidity, but requires rigorous surveillance for the rest of the patient's life because of a relevant incidence of long-term complications, such as endovascular leakage (endoleaks), aneurysm growth, structural failures, graft migration, thrombosis, occlusion of branches and infections. 1,[3][4][5] According to Geller SC, 6 follow-up with imaging studies after endovascular repair should assess three major parameters: (1) aneurysmal diameter; (2) detection and classification of endoleaks, and (3) detection of morphological changes to endoprostheses. Graft occlusion, infection and other potential complications should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with CT, duplex ultrasound is by some authors considered not to be sensitive or specific enough for replacing CT (Mirza et al, 2010;Sun, 2006). Other authors have found that duplex ultrasound may be sufficient in groups of patients, specifically those with a stable aneurysm (Bargellini et al, 2009;Chaer et al, 2009;Nagre et al, 2011). Patel & Carpenter (2010) suggested that duplex ultrasound could be sufficient for long-term follow-up if the initial postoperative CT angiogaphy was normal.…”
Section: Ultrasound In Post-operative Surveillancementioning
confidence: 99%
“…4,5,19,20 CDU has the benefit of being cheaper and less harmful in terms of nephrotoxic contrast and radiation exposure. However, CDU is less sensitive in detecting endoleaks than CTA, and the position, expansion and apposition of the endograft in the proximal neck cannot be investigated.…”
Section: Late Follow-up Cta Scanmentioning
confidence: 99%
“…20 During follow-up, 2.3 -3.0% of the patients will undergo reintervention for a type IA endoleak, 1.0 -5.1% of the patients must be treated for significant device migration (> 10 mm), and type IB endoleak (failure of distal seal) is reason for reintervention in 2.3% of the patients. [21][22][23][24][25] Type IA endoleak and device migration are …”
mentioning
confidence: 99%